Performance Comparison of DSSCs Using Butterfly Pea Flower Extract With Iodine and Peat Water Electrolytes - Gundiawan Gundiawan; Eko Julianto; Muhammad Iwan; Eko Sarwono; Dini Hardiarti (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2026)
The demand for energy in Indonesia continues to increase due to infrastructure development, regional expansion, and highway construction. Solar panels convert solar photon energy into electrical energy and must be exposed to direct sunlight. Dye-sensitized solar cells (DSSC) are a type of solar cell that utilizes photoelectrochemical principles. This study compares the performance of DSSCs using iodine-based electrolytes and peat water electrolytes. The experimental method was conducted directly in the laboratory to test the composition of peat water-based electrolyte with the performance of DSSCs. Extraction of the natural dye from butterfly pea flowers and ethanol at a ratio of 1:10 was soaked for three days in a container covered with plastic at room temperature, producing a wavelength of 410 nm. The test results show that the DSSC with iodine electrolyte achieved an efficiency of 1.42%, which is higher than that of the peat water-based electrolyte, which produced an efficiency of 0.38%. In addition, the maximum power (Pmax) produced by the iodine electrolyte reached 0.0720 W, while peat water produced only 0.0189 W. The test results also indicate that peat water electrolyte has the potential to produce considerable voltage and power at certain times, but its stability is lower than that of iodine electrolyte, which showed more consistent performance.